The combined roles of ADAMTS13 and VWF in murine models of TTP, endotoxemia, and thrombosis - Chauhan, Anil K. (American Society of Hematology, 2008)
Ultralarge von Willebrand factor (UL-VWF) multimers are thought to play a central role in pathogenesis of the disease thrombotic thrombocytopenic purpura (TTP); however, experimental evidence in support of this hypothesis has been difficult to establish. Therefore, to examine directly the requirement for VWF in TTP pathogenesis, we generated ADAMTS13-deficient mice on a TTP-susceptible genetic background that were also either haploinsufficient (Vwf(+/−)) or completely deficient (Vwf(−/−)) in VWF. Absence of VWF resulted in complete protection from shigatoxin (Stx)–induced thrombocytopenia, demonstrating an absolute requirement for VWF in this model (Stx has been shown previously to trigger TTP in ADAMTS13-deficient mice). We next investigated the requirements for ADAMTS13 and VWF in a murine model of endotoxemia. Unlike Stx-induced TTP findings, LPS-induced thrombocytopenia and mortality were not affected by either VWF or ADAMTS13 deficiency, suggesting divergent mechanisms of thrombocytopenia between these 2 disorders. Finally, we show that VWF deficiency abrogates the ADAMTS13-deficient prothrombotic state, suggesting VWF as the only relevant ADAMTS13 substrate under these conditions. Together, these findings shed new light on the potential roles played by ADAMTS13 and VWF in TTP, endotoxemia, and normal hemostasis.